Development and Validation of a Patient-Reported Outcome Scale for Tension-Type Headache - Huang, Jinke; Guo, Weichi; Li, Hui; Xie, Runsheng; Shen, Min; Wang, Huimin (Frontiers in Neurology, 2021)
Objective: To validate a patient-reported outcome (PRO) measure for patients with Tension-type headache (TTH). Methods: Literature analysis, interview and group discussion were performed to develop an initial TTH-PRO. Thereafter, the initial scale was pre-evaluation in a small range of patients with TTH, and the expert panel made necessary adjustments based on the content feedback. The clinical test is carried out by using the adjusted initial scale. Based on the test results, the items were screened by the method of classical test theory to form the final scale, and the performance evaluation indicators such as validity, reliability and responsiveness of the final scale were tested. Results: The final formed TTH-PRO scale contained 3 domains, 6 dimensions, and 30 items. The split-half reliability, Cronbach’s α coefficients and construct validity of the scale were acceptable, as was feasibility. The responsiveness in the physiological domain was fair, but the overall responsiveness still needed further clinical validation. Conclusions: The TTH-PRO scale has been developed with extensive patient input and demonstrates evidence for reliability and validity. It is complementary to existing evaluation indicators of TTH, emphasizing the patient's experience. Further studies are needed to optimize its itmes and to verify its clinical applicability for population in more regions and countries.